Can We AlphaFold Our Way Out of the Next Pandemic?. Issue 20 (1st October 2021) - Higgins, Matthew K.
Graphical abstract: Highlights: Many pathogen surface proteins undergo substantial conformational changes. Structural vaccinology often requires mapping of neutralising antibody epitopes. Structural insights allow antigen stabilisation or epitope grafting approaches. What contributions can AlphaFold 2 make to structure-guided immunogen design? Abstract: The announcement of the outstanding performance of AlphaFold 2 in the CASP 14 protein structure prediction competition came at the end of a long year defined by the COVID-19 pandemic. With an infectious organism dominating the world stage, the developers of Alphafold 2 were keen to play their part, accurately predicting novel structures of two proteins from SARS-CoV-2. In their blog post of December 2020, they highlighted this contribution, writing "we've also seen signs that protein structure prediction could be useful in future pandemic response efforts". So, what role does structural biology play in guiding vaccine immunogen design and what might be the contribution of AlphaFold 2?